Educational Reflections on Islamic Clothing and Character Formation in Muhammadiyah Palangka Raya - Kholisotin, Lilik; Tobroni, Tobroni; Nurhakim, Moh; Karmiyati, Diah (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2025)
This study examines the impact of the implementation of the Islamic dress code on character education at SMA Muhammadiyah Palangka Raya. Using a mixed-methods approach, both quantitative data from surveys and school records, and qualitative data from interviews and focus group discussions were analyzed to explore how the dress code influences student behavior, discipline, and moral development. The quantitative results indicate that 85% of students believe the Islamic dress code promotes self-discipline, with 60% reporting noticeable improvements in their personal behavior. School records also show a 15% reduction in disciplinary incidents and a 7% increase in attendance among students who adhere to the dress code. Qualitative findings reveal that teachers, students, and parents recognize the dress code as a tool for instilling Islamic values, such as respect, responsibility, and modesty. However, challenges such as peer pressure and the conflict between religious dress and fashion trends were noted as significant factors in students' adherence to the dress code. The study highlights the role of the school environment, including the collaboration between teachers, students, and parents, in fostering character education through the dress code. This research contributes to understanding how Islamic dress codes can serve as a practical tool in character development and offers insights for improving the implementation of character education programs in Islamic schools.